Black spruce assimilates nitrate in boreal winter. (21st November 2018) - Koyama, Lina A; Kielland, Knut
Abstract: Winter has long been considered a dormant season in boreal forests regarding plant physiological activity such as nutrient acquisition. However, biogeochemical data clearly show that soil can remain unfrozen with substantial rates of nutrient transformation for several weeks following autumn snowfall. Here we examined nitrate (NO3 – -N) assimilation by black spruce ( Picea mariana (Mill.) Britton, Sterns and Poggenb.) during summer and winter in Interior Alaska to test our hypothesis that this boreal species is able to assimilate NO3 – -N, even at the very low temperatures typical of early winter. Nitrate reductase activity (NRA) was measured in current year needles and fine roots of black spruce as an indicator of NO3 – -N assimilation in the summer and winter at two boreal forest sites. Nitrate concentration in the needles and roots were also measured to determine whether NO3 – -N was available in plant tissue for the enzyme. Nitrate reductase activity and NO3 – -N were detected in needles and roots in the winter as well as the summer. The results of a generalized linear mixed model showed that season had minimal effects on NRA and NO3 – -N concentration in this species. Additionally, the effect of incubation temperature for the NRA assays was tested at 30 °C and −3 °C for samples collected in the winter. Substantial enzyme activity was detected in winter-collected samples, even in incubations conducted at −3 °C. These results indicate that this dominant tree species in the boreal forests of Interior Alaska, black spruce, has the capacity to assimilate NO3 – -N below freezing temperatures, suggesting that the physiological activity required for nitrogen (N) resource acquisition may extend beyond the typical growing season. Our findings coupled to biogeochemical evidence for high microbial activity under the snow also indicate that winter N acquisition should be taken into account when estimating the annual N budgets of boreal forest ecosystems.